Smooth Muscle Cell–targeted RNA Aptamer Inhibits Neointimal Formation - Thiel, William H (Mol Ther, 2016)
Inhibition of vascular smooth muscle cell (VSMC) proliferation by drug eluting stents has markedly reduced intimal hyperplasia and subsequent in-stent restenosis. However, the effects of antiproliferative drugs on endothelial cells (EC) contribute to delayed re-endothelialization and late stent thrombosis. Cell-targeted therapies to inhibit VSMC remodeling while maintaining EC health are necessary to allow vascular healing while preventing restenosis. We describe an RNA aptamer (Apt 14) that functions as a smart drug by preferentially targeting VSMCs as compared to ECs and other myocytes. Furthermore, Apt 14 inhibits phosphatidylinositol 3-kinase/protein kinase-B (PI3K/Akt) and VSMC migration in response to multiple agonists by a mechanism that involves inhibition of platelet-derived growth factor receptor (PDGFR)-β phosphorylation. In a murine model of carotid injury, treatment of vessels with Apt 14 reduces neointimal formation to levels similar to those observed with paclitaxel. Importantly, we confirm that Apt 14 cross-reacts with rodent and human VSMCs, exhibits a half-life of ~300 hours in human serum, and does not elicit immune activation of human peripheral blood mononuclear cells. We describe a VSMC-targeted RNA aptamer that blocks cell migration and inhibits intimal formation. These findings provide the foundation for the translation of cell-targeted RNA therapeutics to vascular disease.